THE THE EFFECT OF GENIALLY-BASED INTERACTIVE MEDIA ON FIFTH-GRADE STUDENTS’ INTEREST IN IPAS LEARNING - Repanda Salna Pegareta; Dya Ayu Agustiana Putri; Nourma Oktaviarini (Jurnal Tatsqif, 2026)
Students’ interest in learning IPAS needs to be supported through learning media that can present concepts in a more visual, interactive, and engaging way. This study examined the effect of Genially-based interactive media on fifth-grade students’ interest in learning IPAS, particularly on food chain material. A quantitative quasi-experimental design with a nonequivalent control group was employed. The participants were 46 fifth-grade students, consisting of 21 students in the experimental class and 25 students in the control class. The experimental class learned through Genially-based interactive media, while the control class received conventional instruction. Students’ learning interest was measured using a 20-item questionnaire administered before and after the intervention. The instrument showed strong internal consistency, with a Cronbach’s alpha value of 0.944. Assumption testing indicated that the data were normally distributed and homogeneous. The pretest comparison showed no significant difference between the experimental and control groups, t(44) = 0.799, p = 0.429, indicating relatively similar initial learning interest. The posttest comparison showed a significant difference between the groups, t(44) = 4.146, p < .001. These findings suggest that Genially-based interactive media was associated with higher students’ learning interest in IPAS. The results should be interpreted within the limits of the nonequivalent group design and the use of questionnaire-based data.